Alienation of the Disabled: Causative Factors, Mechanisms, and Patterns of Reaction Responses - Agarawal, Aakanksha (JOURNAL OF INDIAN EDUCATION, 2010)
The human society has, in general, always tended to isolate and segregate people with disabilities. Not just in India, across the world, individuals with disabilities are a discrete and insular minority, and subjected to unequal treatment. The prejudices they endure are generally based on characteristics that are beyond their control and result from stereotypical assumptions and biases in the society. Relegated to a position of psychosocial, cultural, economic and political powerlessness, the disquiet of social discrimination severely affects their selfbelief, esteem, and social behaviour. Diverse patterns of alienation reactions emerge, dominated by a sense of meaninglessness, normlessness and severe isolation. As a result, they neither realise their potential nor get an opportunity to participate and contribute to the society. The present essay, in its first part, uncovers the causative factors which produce alienation in people with disabilities, and in its latter part, portrays the effects of social discrimination on their psychosocial, cultural, economic and political well-being.